Perspectives on modern South Asia : a reader in culture, history, and representation - Visweswaran, Kamala (Global perspectives, 2011)
"Perspectives on Modern South Asia presents an exciting core collection of essays drawn from anthropology, literary and cultural studies, history, sociology, economics, and political science to reveal the complexities of a region that is home to a fifth of humanity. Presents an interdisciplinary overview of the origins and development of the eight nations comprising modern South Asia: Afghanistan, Bhutan, Bangladesh, India, the Maldives, India, Pakistan, and Sri Lanka. Explores South Asia's common cultures, languages and religions and their relationship to its ethnic and national differences. Features essays that provide understandings of the central dynamics of South Asia as an important cultural, political, and economic region of the world."